From transitions to stagnation. Revisiting democratization in the work of Guillermo O'Donnell (2016)
This paper focuses on reconstructing the influential contributions from political scientist Guillermo O'Donnell to studies on the processes of democratization. In order to do this, it discusses his main analytical and conceptual elaborations placing them in the political and historical context in which they were developed. It further analyses their relation to other theoretical developments and ideological debates that have followed them. In particular, this review focuses, first, on the period of transitions to democracy in Latin America, showing how O'Donnell's theoretical constructs were part of his wider political and normative commitments. Such commitments are subsequently reflected in the political concerns, research interests and conceptual contributions by the author in the post-transitional period, related to his ideas on delegate democracy and horizontal accountability, both discussed in the second part of this review.